Risk factors associated with preterm labor in AlDiwaniyah province: case control study - Abdulzahra Mutar, Suaad; Abdulhassan Raffas, Hayfaa; Abduljabbar Lateef, Nabaa (International Journal of Psychosocial Rehabilitation, 2020)
Background: Many preterm children will experience healthy life; however, a significant proportion of them will suffer long term disability because of serious complications during the perinatal period. On the other hand, families with preterm babies are going to suffer both psychologically and economically and the burden of preterm babies on national health budget is also significant. Therefore, prevention of preterm labor will reduce patient suffering and reduce cost of health budget allocated to obstetric practice. Aim of the study: The current study was planned and conducted in the mid-Euphrates region of Iraq in order to identify the most frequent risk factors in association with preterm labor. Patients and methods: The study included 30 women with preterm labor serving as a study group and 30 women with term labor serving as control group. A questionnaire form included age of mother, occupation, mode of delivery, residency, birth weight, history of antenatal care, estimation of body mass index (BMI), history of polyhydramnios, pregnancy induced hypertension, preeclampsia, essential hypertension, breech presentation, previous cesarean section, transverse lie, oligohydramnios, cervical incompetence, diabetes mellitus, short interpregnancy interval, previous history of preterm labor, uterine distortion, systemic lupus erythematosus (SLE), placental abruption, urinary tract infection (UTI), uterine fibroid and twin pregnancy. Results: it was found that the frequencies of women less than 20 years and women more than > 35 years were significantly higher in preterm group in comparison with study group (P < 0.001). It was found that the frequencies of obese women and underweight women were significantly higher in preterm group in comparison with study group. The frequency of women with irregular antenatal care was higher in preterm group in comparison with term group, 63.3 % versus 26.7 %, respectively, in a highly significant manner (P = 0.004); the odds ratio (OR) was 4.75 with 95 % of 1.58 -14.25. Cervical incompetence, diabetes mellitus and short inter-pregnancy intervals were limited to women with preterm labor and represented significant risk factors for preterm labor (P < 0.05), with approximate OR of 16.18, 13.16 and 19.47. Conclusion: relative extreme of reproductive age, abnormal body mass index, irregular antenatal care, diabetes mellitus, cervical incompetence and short inter-pregnancy intervals were the principal risk factors of preterm labor.